2020
DOI: 10.3389/fped.2019.00546
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Isolated ACTH Deficiency Caused by TBX19 Gene Mutation: A Family Report

Abstract: Congenital isolated adrenocorticotropic hormone deficiency (CIAD) is a rare disorder that may be conducive to hypoglycemia, cholestasis, and seizures. We reported on two siblings with a homozygous mutation of the TBX19 gene, C.377 (exon2) C>T, p. P126L. Their parents had heterozygous mutations on the same locus. Glucocorticoid supplementary therapy was effective, but the treatment became delayed due to inaccessibility, which resulted in entirely different clinical outcomes for the siblings. The older brother d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…TBX19 gene is a member of the phylogenetically conserved T‐box gene family and encodes transcription factors involved in the regulation of developmental processes, which have been reported to regulate the behavior of humans and other animals (Zhu et al, 2017). Mutations in the TBX19 gene cause isolated ACTH deficiency (Peng et al, 2020). A 9466 bp DUP was located in a 70 kb haplotype shared in Chinese breeds, and was highly differentiated from the haplotypes of European pigs and all wild boars (Figure 4b) (Zhu et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…TBX19 gene is a member of the phylogenetically conserved T‐box gene family and encodes transcription factors involved in the regulation of developmental processes, which have been reported to regulate the behavior of humans and other animals (Zhu et al, 2017). Mutations in the TBX19 gene cause isolated ACTH deficiency (Peng et al, 2020). A 9466 bp DUP was located in a 70 kb haplotype shared in Chinese breeds, and was highly differentiated from the haplotypes of European pigs and all wild boars (Figure 4b) (Zhu et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that secondary and tertiary AI may be latent or their onset may often be slow; congenital AI may become apparent around puberty (especially in septo-optic dysplasia [7] or hypopituitarism associated with perinatal problems [8]), while acquired AI can occur months to years after intracranial radiation [9] or traumatic brain injury [10,11]. Severe hypoglycemia in the neonatal period is rather exceptional and can be seen in congenital isolated ACTH deficiency caused by a TBX19 gene mutation [12].…”
Section: Primary Adrenal Insufficiencymentioning
confidence: 99%
“…Transcription factor inactivation can contribute to metabolic disorders and diseases, as demonstrated by recent studies ( 7 ). Specifically, the TBX19 gene is critical for brain cognition ( 8 ). The mutation (Glu280Asp) in TBX19 is associated with isolated ACTH deficiency (IAD) and cognitive impairment reported by Charnay et al Additionally, the study found that mutations in the TBX19 gene can occur at multiple sites, with multiple pathological effects.…”
mentioning
confidence: 99%